AN ANALYSIS OF DEIXIS IN JOHN CLAYTON MAYER’S YOU ARE GONNA LIVE FOREVER IN ME SONG - Dina Nur'Aini Zahra; Nai Supartini Atmawidjaja (PROJECT (Professional Journal of English Education), 2024)
Language is more than a tool used to communicate between humans, but also becomes an inseparable part that makes language have various meanings and can be enjoyed by humans. One of the fields that humans can learn from language is pragmatics, which has a sub-study of deixis. Deixis is a sub-study of pragmatics that studies how to study a word related to name, place, time, position, etc. Deixis is found in many media around humans, one of which is music as an entertainment medium. In this study, the author is interested in conducting a deixis analysis of the song with the title "You're Gonna Live Forever in Me" which was sung by John Clayton Mayor in 2017 and is popular again in 2022. In this study, the author employed a descriptive qualitative method, which in contrast to an experimental design, was designed solely to describe a variable, set of symptoms, or condition. There are instances in this study where the claims are confirmed, although they are not frequently. This research used song lyrics entirely to obtain the research data. The results of the analysis are presented using tables to make it easier for readers to understand the results of the data and the types of deixis that the author has analyzed. As a result, the authors found 4 out of 5 deixes that the authors analyzed with each frequency. Personal Deixis 58%, as the highest frequency, Temporal Deixis 20%, Spatial Deixis 20%, Discourse deixis 0% and Social Deixis 2%.